2004
DOI: 10.1038/sj.onc.1208226
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of the net inhibitory domain (NID) is stimulated by PIAS1 and has a negative effect on the transcriptional activity of Net

Abstract: Net (Elk-3, Sap-2, Erp) and the related ternary complex factors Elk-1 and Sap-1 are effectors of multiple signalling pathways at the transcriptional level and play a key role in the dynamic regulation of gene expression. Net is distinct from Elk-1 and Sap-1, in that it is a strong repressor of transcription that is converted to an activator by the Ras/Erk signalling pathway. Two autonomous repression domains of Net, the NID and the CID, mediate repression. We have previously shown that the corepressor CtBP is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…4A). The bands of ~14 and ~50 kDa are consistent, respectively, with the size of protein detected in COS-7 cells transfected with an Elk3d expression vector (data not shown) and with full-length Elk3 (Giovane et al, 1997), while the larger bands may correspond to the sumoylated conjugates of Elk3 detected in COS-7 cells transfected with both Elk3 and SUMO-1 cDNAs (Wasylyk et al, 2005). In adult heart, an additional band of ~29 kDa of unknown identity was also detected (Fig.…”
Section: Resultssupporting
confidence: 76%
“…4A). The bands of ~14 and ~50 kDa are consistent, respectively, with the size of protein detected in COS-7 cells transfected with an Elk3d expression vector (data not shown) and with full-length Elk3 (Giovane et al, 1997), while the larger bands may correspond to the sumoylated conjugates of Elk3 detected in COS-7 cells transfected with both Elk3 and SUMO-1 cDNAs (Wasylyk et al, 2005). In adult heart, an additional band of ~29 kDa of unknown identity was also detected (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Our data reveal that Ets-1 indeed undergoes SUMO modifications, with Ubc9 being able to enhance sumoylation of Ets-1. We also examined whether PIAS proteins can act as E3 ligases for SUMO modification of Ets-1, since these proteins can enhance SUMO conjugation of many transcription factors, including ETS transcription factors, such as Elk-1 (Yang and Sharrocks, 2005) and Net (Wasylyk et al, 2005). Our data show that PIASy is able to interact and to enhance sumoylation of Ets-1.…”
Section: Discussionmentioning
confidence: 94%
“…SUMO modification appears to play a role in a variety of cellular processes including protein-protein interaction, subcellular localization, protein stabilization and transcriptional regulation (Dohmen, 2004). A large number of SUMO target proteins have been identified, including several members of the Ets transcription factors family (Chakrabarti et al, 2000;Yang et al, 2003;Degerny et al, 2005;Leight et al, 2005;van den Akker et al, 2005;Wasylyk et al, 2005). Recently, we reported that the ERM Ets protein is sumoylated and that sumoylation of ERM represses its transcriptional activity (Degerny et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…The CID interacts with the corepressor E1A C-terminal binding protein, which represses transcription through histone deacetylase activity. The NID interacts with the sumoylation E2 and E3 enzymes Ubc9 and PIAS1, and NID sumoylation on lysine 162 increases repression by Net (62). Interestingly, sumoylation of Elk-1 leads to recruitment of the histone deacetylase HDAC2 and transcriptional repression (66).…”
mentioning
confidence: 99%